(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Postoperative contra lateral morbidity following fracture fixation surgery is rare due to hemilithotomy placement on traction table. Following a typical orthopedic femoral nailing, we should note a case of unexplained typical peroneal nerve palsy formed on the contra lateral side, manifesting with drop foot. Case report: After prolonged femoral nailing, a 32-year-old male suffered an uncommon common peroneal nerve palsy that manifested itself toward lateral drop foot. This iatrogenic and intermittent disorder was delineated to be position-related neuropraxia after neurophysiological analysis and review of applicable literature. Conclusion: Place modification at intervals or complete avoidance of excessive hyperflexion of the knee is advised to prevent typical peroneal nerve morbidity against the lateral.